Third-Party Borehole Seismic Experiments during the Ocean Drilling Program - R. A. Stephen; S. A. Swift; S. T. Bolmer; H. Hoskins (Scientific Drilling, 2007)
No abstract available. doi:10.2204/iodp.sd.s01.08.2007